Wildfire : grassroots revolts in Israel in the post-socialist era - Lehman-Wilzig, Sam N. (Albany : State University of New York Press, 1992)
Annotation Lehman-Wilzig (political studies, Bar-Ilan U.) describes Israeli grassroots extra-parliamentarianism and analyzes the impact of the most important alternative systems: illegal settlement activity, a huge underground economy, pirate cable TV stations, Black medicine, anti-religious as well as anti-secular activity, and a growing demand for electoral reform and constitutionalization of the Israeli polity. Paper edition (unseen), $12.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Part III: Conclusions -- Potential Grassroots Fires -- Conflagration? Fireproofing the System -- Loyalty, Voice, and ltex It: A Theory of Alter-Politics -- Between Past and Future: Israel's Grassroots Revolts in Historical Cross-Comparative Perspective -- Back Matter -- Bibliography -- Index -- Back Matter.
Includes bibliographical references (pages 177-185) and index.
Print version record.
English.
JSTOR
Keywords: Political participation -- Israel; Israel -- Politics and government; Israel -- Social conditions; Participation politique -- Israël.; Israël -- Politique et gouvernement; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Political participation; Politics and government; Social conditions; Israel